1992
DOI: 10.1111/j.1751-1097.1992.tb09710.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriorhodopsin Reconstituted From Two Individual Helices and the Complementary Five‐helix Fragment Is Photoactive

Abstract: Bacteriorhodopsin (bR), a light-driven proton pump, consists of a bundle of seven membrane-spanning alpha-helices connected to each other by short extramembranous loops. Previously it has been shown that bR can be reconstituted from three fragments corresponding to the first helix, the second helix, and the remaining five helices, and that this reconstituted material reforms the native structure of bR. In this study, it is shown that the native function is also recovered. Low-temperature spectroscopy was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Bacteriorhodopsin helix assembly and activity is therefore largely governed by helical packing interactions alone, being remarkably insensitive to both structural perturbations of the inter-helical loops and to helical connectivity, consistent with previous observations (Kahn and Engelman 1992; Kataoka et al 1992; Marti 1998; Kim et al 2001). Currently, the principles of membrane protein folding are poorly understood relative to soluble proteins.…”
Section: Resultssupporting
confidence: 90%
“…Bacteriorhodopsin helix assembly and activity is therefore largely governed by helical packing interactions alone, being remarkably insensitive to both structural perturbations of the inter-helical loops and to helical connectivity, consistent with previous observations (Kahn and Engelman 1992; Kataoka et al 1992; Marti 1998; Kim et al 2001). Currently, the principles of membrane protein folding are poorly understood relative to soluble proteins.…”
Section: Resultssupporting
confidence: 90%
“…Since helices B, C, and G are connected through a hydrogen bonding network (1), deprotonation of Schiff base (helix G) and protonation of Asp-85 (helix C) would perturb their interaction. In helix B, there are Tyr-57 and Tyr-64, which are expected to be hydrogen-bonded with residues in helix C. Therefore, it is plausible that helix B is affected by the environmental change generated near the Schiff base in the M intermediate earlier than helix F. bR reconstituted from two individual helices corresponding to A and B, and the remaining five-helix fragment, produces two different M photoproducts, also suggesting the importance of B helix at M formation (44).…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is supported by a number of studies that have shown that fragments of membrane proteins in which the loops between helices are disrupted or absent can retain the ability to self-assemble in a membrane (4). Experiments have shown that the bacteriorhodopsin molecule can be cut in several loops and reassembled (6,7), and related experiments on other proteins have demonstrated that coexpression of fragments cut in loop regions results in functional proteins inserted into membranes (see table in ref. 4).…”
Section: Resultsmentioning
confidence: 99%